3258 The Relationship Between the Severity of Influenza-Related Illness and Timing of Seasonal Influenza Vaccination in Hospitalized Patients with Influenza. (27th March 2019) - Haston, Julia; Garg, Shikha; Campbell, Angela; Ferdinands, Jill; Farley, Monica; Anderson, Evan
Abstract : OBJECTIVES/SPECIFIC AIMS: The overall goal of this project is to determine whether timing of seasonal influenza vaccination affects the severity of illness in vaccinated individuals who are hospitalized with influenza. This will be assessed with the following aims: 1. To determine whether differences in demographic and clinical characteristics exist among patients with short duration between seasonal influenza vaccination and influenza-related hospitalization and those with longer duration. 2. To determine whether time between seasonal influenza vaccination and hospitalization is associated with the duration of influenza-related hospitalization. 3. To determine whether time between seasonal influenza vaccination and hospitalization is associated with the rate of influenza-related ICU admission among patients hospitalized with influenza. 4. To determine whether time between seasonal influenza vaccination and hospitalization is associated with the rate of influenza-related death among adults hospitalized with influenza. METHODS/STUDY POPULATION: The Influenza Hospitalization Surveillance Network (FluSurv-NET) is a surveillance platform of influenza-related hospitalizations through the CDC Emerging Infections Program (EIP). FluSurv-NET conducts active surveillance for influenza-related hospitalizations of both children and adults in selected counties in California, Colorado, Connecticut, Georgia, Maryland, Michigan, Minnesota, Ohio, Oregon, New Mexico, New York, Tennessee, and Utah with a total catchment population of over 27 million people (~9% of the US population). Using this platform, we will retrospectively evaluate four influenza seasons using FluSurv-NET data to look at the timing of influenza vaccination and severity of illness among patients with influenza-related hospitalization. We will conduct a multivariate analysis to assess for differences in severe outcomes including duration of hospitalization, ICU admission, and death among patients with varying lengths of time between influenza vaccination and influenza-related hospitalization. Separate analyses will be performed among different age groups and influenza type/subtypes, as well as specific seasons as a surrogate for most common circulating strain. RESULTS/ANTICIPATED RESULTS: We hypothesize that patients with chronic medical conditions and those at the extremes of age will have a longer duration between vaccination and hospitalization as they are more likely to get vaccinated earlier. We also hypothesize that patients with longer duration between seasonal influenza vaccination and hospitalization will have a longer duration of hospitalization and a higher rate of other severe outcomes (e.g., ICU admission, death). Such data would suggest that immune protection wanes during the influenza season. DISCUSSION/SIGNIFICANCE OF IMPACT: Limited data suggest that vaccine-induced influenza immunity may wane during the influenza season. It is not known whether the impact of influenza vaccination upon severity of disease might wane with increasing time between vaccination and influenza infection. In contrast to many previous studies evaluating vaccine effectiveness which have assessed medically-attended influenza illness as a primary outcome, our dataset is a large cohort of hospitalized patients which allows us to assess rare yet critical outcomes such as ICU admission and death. This study will also have a substantially larger amount of pediatric data than previous studies, which will provide the opportunity to determine whether timing of vaccination affects children and adults differently. Improving our understanding of whether influenza vaccine-induced protection might wane over time could ultimately impact U.S. influenza vaccination policy resulting in decreased morbidity and mortality attributed to influenza each season.